HTML, CSS and JavaScript for beginners a web design course - Svekis, Laurence (Packt Publishing, 2019)
"This course starts from scratch, teaches you how to create websites, and covers everything from the basic syntax, all the common tags used to develop web content, and how and where you can write HTML, top resources and links included. You'll learn about HTML structure within web pages; explore HTML5 semantic elements; build your own HTML template; create HTML lists, hyperlinks, and add images; build tables for even more HTML structure; create forms with in-depth form examples and HTML tag explanations; add iframes and more cool HTML elements; create your own mini HTML site using only HTML; and everything you want to know about CSS, JavaScript, JavaScript Document Object Model (DOM), JSON, AJAX, and jQuery."--Resource description page
Title from resource description page (Safari, viewed March 8, 2019)
Keywords: Web site development; HTML (Document markup language); Cascading style sheets; JavaScript (Computer program language); Web sites -- Design; Sites Web; Développement; HTML (Langage de balisage); Feuilles de style en cascade; JavaScript (Langage de programmation); Sites Web; Conception; HTML; Web sites; Design